Hydrocarbon exploration - Ganat, T.A.-A.O. (Springer, 2020)
Hydrocarbon (Oil and gas) exploration is the search by geologists and geophysicists for oil and natural gas deposits underground for millions of years. The hydrocarbon exploration is congregated under the skill of petroleum geology. Â© The Author(s), under exclusive license to Springer Nature Switzerland AG 2020.